The Male Body, Beauty and Aesthetics in Modern British Culture - Deslandes, Paul R. (History compass, 2010)
This article examines the topics of the male body, beauty and beauty culture in nineteenth- and twentieth-century Britain. By exploring work ranging from the study of sport and physical culture to disability and disfigurement in the First World War and queer history, this piece argues that historians should place at the centre, not marginalize, examinations of physical appearance, aesthetics and the adornment and manipulation of the body. Such an approach, it is argued, will only serve to enhance the field of masculinity studies and enrich understandings of the British past.